Design and synthesis of nanostructures to study the specific molecular recognition and effector Cell activation in the immunological responses to amoxicillin - Ayane, Amene Tesfaye (UMA Editorial, 2022)
Amoxicillin (AX) is the penicillin currently regarded as the main culprit in eliciting allergic reactions. According to hapten hypothesis, AX immunogenicity can only be gained by forming covalent conjugates with proteins. The diagnosis of immediate allergic reactions (IRs) to AX in clinical practice is based mainly on in vivo and in vitro methods. Due to the non-optimal sensitivity of skin tests, drug provocation test is considered the gold standard to establish the diagnosis, which is risky to the patient and not recommended in patients with a history of life-threatening reactions. In vitro tests are based on the determination of specific IgE (sIgE) (immunoassays), with the commercial ImmunoCAP only detecting 20% of allergic patients, and on the quantification of basophil activation after stimulation with the culprit drug, showing sensitivity around 50%. Among the factors affecting such low sensitivity could be the fact that correct antigenic determinant and/or conjugates are not incorporated into in vitro tests. In this thesis we propose the use of structural activity approach to nano-engineer the structural properties of conjugates to be appropriate for the crosslinking of sIgE bound to high-affinity receptor on basophils or mast cells (MCs). To attain this, we made use of dendrimer-based structures to generate three different structures called: (1) Dendrimeric Antigens (DeAns); (2) Bidendron Antigens (BiAns); and (3) Bidendron Antigens of different generations (BiAn-dGn), to obtain a library of well-defined nanoarchitectures, with variation in the size and numbers of antigenic determinants. The DeAns were prepared by decoration of terminal amino groups of dendrimers with AX. The BiAns and BiAn-dGn were constructed based on AX-decorated dendrons spaced with polyethylene glycol (PEG) chains of distinct lengths (600 - 12000 Dalton).
The ability of AX-sIgE to recognize the nanostructures was evaluated by competitive radioimmunoassay using sera from AX-allergic patients. The result indicted that all nanostructures were recognized by AX-sIgE. Allergenic activities were assessed using bone marrow-derived MCs, primed with mouse anti-AX IgE, and humanized RBL-2H3 cells, primed with polyclonal antibodies from sera of AX-allergic patients and tolerant subjects. Activation of the effector cells degranulation was observed in DeAn based on generation 3 and above (estimated molecular diameter of 4.6 nm) and in BiAn containing a PEG polymeric spacer longer than 6000 Dalton. In conclusion, activation of cellular response to AX can happen with an allergenic structure bearing at least two antigenic determinants separated by the optimal minimal distance between them, which highlights the importance of the antigen size.
Keywords: Alergia; Universidad de Málaga - Tesis doctorales; Antibióticos - Síntesis; Nanoestructuras; Dendrímeros; Allergy; Amoxicillin; Nanostructure; Dendrimer